Perioperative anidulafungin combined with triazole prophylaxis for the prevention of early invasive candidiasis in lung transplant recipients. Issue 4 (23rd July 2021) - Sartain, Emily; Schoeppler, Kelly; Crowther, Barrett; Smith, Joshua B.; Abidi, Maheen Z.; Grazia, Todd J.; Steele, Mark; Gleason, Terri; Porter, Krista; Gray, Alice
Abstract: Background: Invasive candidiasis (IC) is a substantial cause of morbidity and mortality among lung transplant recipients (LTRs). Postoperative factors include prolonged hospital stay, central lines, delayed chest closure, and dehiscence increase IC risk. Correspondingly, current guidelines propose targeted IC coverage early posttransplant with fluconazole or an echinocandin. Methods: This retrospective analysis was performed on LTRs from January 2016 to January 2020 and evaluated effectiveness of a recent protocol utilizing perioperative anidulafungin for early IC prevention in addition to long‐term triazole antifungal prophylaxis. Prior to this protocol, patients were primarily established on itraconazole prophylaxis alone. The primary endpoint was proven or probable IC within 90 days after transplant. Multivariable logistic regression modeling was used to assess risk factors for invasive fungal infection (IFI). Results: Among 144 LTRs, there was a numerically lower incidence of IC in the protocol group, although not statistically significant (6% vs. 13%, p = 0.16). Incidence of proven or probable IFI was 7.5% in the protocol cohort and 19.5% in the pre‐protocol cohort ( p = 0.038). In multivariable analysis, when controlling for lung allocation score (OR 1.04, 95% CI 1.01–1.08), donor perioperative culture with fungal growth (OR 2.92, 95% CI 1.02‐8.92), and dehiscence (OR 3.54, 95% CI 1.14–10.85), protocol cohort was not significantly associated with IFI (OR 0.41, 95% CI 0.12–1.23). Conclusions: To our knowledge, this is the first study investigating combination triazole/echinocandin use in the early post‐lung transplant period. These findings demonstrate that in‐hospital anidulafungin offers unclear benefit for early IC prevention when used in combination with triazole prophylaxis.